Pilomatrix Carcinoma in a Patient With Type 1 Myotonic Dystrophy: A Case Report. (8th January 2020) - Zhu, Sarah L.; Choi, David; Santos, Jenny; Jackson, Bernard S.; McRae, Matthew
This is the first report of pilomatrix carcinoma in a man with C282Y myotonic dystrophy type 1. This pilomatrix carcinoma had originally presented as a rapidly growing recurrence of a histopathologically confirmed pilomatrixoma, removed a year prior. On examination, the fungating mass had measured 10 × 23 cm. A wide local resection with removal of suspicious lymph nodes was preformed, and the resulting defect was reconstructed with a latissimus dorsi myocutaneous flap and skin graft. Histologic investigation of the excised mass confirmed the diagnosis of pilomatrix carcinoma. This is the first reported case of pilomatrix carcinoma in a patient with a genetic condition that often presents with scalp pilomatrixomas. Potential implications of myotonic dystrophy on developing pilomatrix carcinoma are discussed.